Indonesian version of the motorcycle rider behaviour questionnaire: cross-cultural adaptation and validation - Setyowati, Dina Lusiana; Setyaningsih, Yuliani; Suryawati, Chriswardani; Lestantyo, Daru (International Journal of Public Health Science (IJPHS), 2024)
The study revealed that safety behaviour played a significant role in traffic accidents. One of the primary concerns pertains to the implementation of driving safety practices and the associated risks they pose on the roadways. Numerous studies have been conducted in various countries to investigate the negative consequences of safety behaviour on both victims and nations. These studies have employed the motorcycle rider behaviour questionnaire (MRBQ), a widely utilized instrument to evaluate and mitigate the prevalence of hazardous behavior in road driving scenarios. Nevertheless, the validity of this method has not been established in the Indonesian setting. The present study aimed to assess the reliability and construct validity of the Indonesian adaptation of the MRBQ. The study recruited a cohort of 37 students representing a diverse range of academic disciplines from 12 distinct universities. The study's findings revealed that the validity values obtained varied between a minimum of <0.001 and a maximum of 0.987. Additionally, the reliability of the 27 items was assessed using Cronbach's alpha coefficient, which yielded a value of 0.742. The present study confirms the reliability of the Indonesian version of the MRBQ, as well as the acceptability of its construct validity, which exceeds the threshold of 0.70. Therefore, this tool can be valuable for evaluating driving safety behaviour.